Identity-Making Through Cree Mathematizing - Stavrou, Stavros Georgios; Murphy, M. Shaun (Canadian Journal of Education/Revue canadienne de l'éducation, 2019)
We describe mathematics classroom teaching practice in an urban Canadian prairie Cree-bilingual school using the term Cree mathematizing, which, to us, means (re)considering Euro-Western school mathematics from the perspectives of the Cree people engaging with the content. Cree mathematizing takes the form of classroom lessons in which mathematical terms are translated between English and Cree, shared through stories situated in time, place, and relationships, and contextualized by the experiences of the students and teachers. In terms of the narrative conception of identity-making, Cree mathematizing is a process of engaging in school mathematics that necessitates Cree educators and students to understand themselves as producing mathematics through their unique experiences and stories, making Cree mathematizing a partial representation of identity. We argue that Cree mathematizing is a subversive practice that challenges the ways Euro-Western school mathematics is taught as a culture-free, apolitical, and decontextualized endeavour that is devoid of human narratives of experience. Keywords: Indigenous mathematics education, Indigenization, narrative inquiry, Aboriginal education